The auxiliary glutamate receptor subunit dSol-1 promotes presynaptic neurotransmitter release and homeostatic potentiation - Kiragasi, Beril (Proc Natl Acad Sci U S A, 2020)
Presynaptic glutamate receptors (GluRs) modulate neurotransmitter release and are physiological targets for regulation during various forms of plasticity. Although much is known about the auxiliary subunits associated with postsynaptic GluRs, far less is understood about presynaptic auxiliary GluR subunits and their functions. At the Drosophila neuromuscular junction, a presynaptic GluR, DKaiR1D, localizes near active zones and operates as an autoreceptor to tune baseline transmission and enhance presynaptic neurotransmitter release in response to diminished postsynaptic GluR functionality, a process referred to as presynaptic homeostatic potentiation (PHP). Here, we identify an auxiliary subunit that collaborates with DKaiR1D to promote these synaptic functions. This subunit, dSol-1, is the homolog of the Caenorhabditis elegans CUB (Complement C1r/C1s, Uegf, Bmp1) domain protein Sol-1. We find that dSol-1 functions in neurons to facilitate baseline neurotransmission and to enable PHP expression, properties shared with DKaiR1D. Intriguingly, presynaptic overexpression of dSol-1 is sufficient to enhance neurotransmitter release through a DKaiR1D-dependent mechanism. Furthermore, dSol-1 is necessary to rapidly increase the abundance of DKaiR1D receptors near active zones during homeostatic signaling. Together with recent work showing the CUB domain protein Neto2 is necessary for the homeostatic modulation of postsynaptic GluRs in mammals, our data demonstrate that dSol-1 is required for the homeostatic regulation of presynaptic GluRs. Thus, we propose that CUB domain proteins are fundamental homeostatic modulators of GluRs on both sides of the synapse.